2020
DOI: 10.1111/mec.15675
|View full text |Cite
|
Sign up to set email alerts
|

Using ITS2 metabarcoding and microscopy to analyse shifts in pollen diets of honey bees and bumble bees along a mass‐flowering crop gradient

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 82 publications
4
19
0
Order By: Relevance
“…Metabarcoding was able to detect many of the most abundant taxa identified with microscopy, often in similarly high proportions. Previous studies have found a positive correlation between the relative abundance of taxa identified in pollen samples by microscopy an metabarcoding, mostly for dominant taxa (Bänsch et al, 2020;Smart et al, 2017). The overlap in taxa identified by both methods was 21 families, representing 67.7% of the families detected by microscopy, and 12 genera, representing 44.4% of genera detected by microscopy.…”
Section: Pollen Metabarcoding Comparison With Microscopymentioning
confidence: 76%
“…Metabarcoding was able to detect many of the most abundant taxa identified with microscopy, often in similarly high proportions. Previous studies have found a positive correlation between the relative abundance of taxa identified in pollen samples by microscopy an metabarcoding, mostly for dominant taxa (Bänsch et al, 2020;Smart et al, 2017). The overlap in taxa identified by both methods was 21 families, representing 67.7% of the families detected by microscopy, and 12 genera, representing 44.4% of genera detected by microscopy.…”
Section: Pollen Metabarcoding Comparison With Microscopymentioning
confidence: 76%
“…Still, we claim that in the most important bumble bee forage plants, the proportional quantification of the reads produces a fairly good result. Bänsch et al [ 61 ] also used the DNA metabarcoding with reads from ITS2 region sequences to quantify the bumble bee-collected pollen but reminded that the interpretation must take the specific limitations of the outcome into account.…”
Section: Discussionmentioning
confidence: 99%
“…Our primers further demonstrated unexpected detection of novel Encarsia and Eretmocerus parasitoid species in the African cassava and noncassava fields, however the true genetic and species diversity of these minute parasitoids will require independent assessment for confirmation, such as to include the standard barcode COI gene region using standard primers (e.g., C_LepFoIF/C_LepFoIR; Woodcock et al, 2013) as internal control. Nevertheless, understanding of trophic interactions between crop hosts, pest/beneficial insects and their potential biological control agents represents a molecular ecological network research area that could yield significant insights via metabarcoding approach (e.g., Bansch et al, 2020;Evans, Kitson, Lunt, Straw, & Pocock, 2016;Sow et al, 2019).…”
Section: Discussionmentioning
confidence: 99%